2022
DOI: 10.1039/d1tb02446a
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dot composites for bioapplications: a review

Abstract: Carbon dots (CDs) have received extensive attention in the last decade for their excellent optical, chemical and biological properties. In recent years, CDs composites have also received significant attention due...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 401 publications
(773 reference statements)
0
19
0
Order By: Relevance
“…Metal-doped and hybrid CDs with unique properties have illustrated promising biomedical potentials because of their significant antibacterial, antifungal, antioxidant, and photothermal/photodynamic therapy effects [ 14 ]. Peng et al [ 34 ] discussed recent advancements related to CD composites such as metal CDs, multi-component CDs, non-metallic inorganic CDs, and organic CDs with various bio-applications, namely, drug delivery and biosensing/bioimaging [ 34 ]. In one study, biowaste-derived CDs/hydroxyapatite nanocomposites synthesized from sugarcane bagasse char precursor via a hydrothermal technique could be deployed as nanocarriers for delivery of acetaminophen, with a loading capacity of ~48.5% [ 35 ].…”
Section: Waste To Wealth: Biowaste-derived Cds With Biomedical Potentialmentioning
confidence: 99%
“…Metal-doped and hybrid CDs with unique properties have illustrated promising biomedical potentials because of their significant antibacterial, antifungal, antioxidant, and photothermal/photodynamic therapy effects [ 14 ]. Peng et al [ 34 ] discussed recent advancements related to CD composites such as metal CDs, multi-component CDs, non-metallic inorganic CDs, and organic CDs with various bio-applications, namely, drug delivery and biosensing/bioimaging [ 34 ]. In one study, biowaste-derived CDs/hydroxyapatite nanocomposites synthesized from sugarcane bagasse char precursor via a hydrothermal technique could be deployed as nanocarriers for delivery of acetaminophen, with a loading capacity of ~48.5% [ 35 ].…”
Section: Waste To Wealth: Biowaste-derived Cds With Biomedical Potentialmentioning
confidence: 99%
“…Ring structures of carbon atoms with either alternate single and triple bonds (polyynic) or consecutive double bonds (cumulenic) form a new family of carbon allotropes known as cyclo­[ n ]­carbons. , This allotrope of carbon is now in the limelight among researchers because of its potential applications for various molecular devices. Cyclo­[ n ]­carbons are observed in the condensed phase, and their properties such as electronic structure, optical spectra, and aromaticity have already been reported using theoretical methods. The cation-radicals of even-number cyclocarbons were recently generated experimentally in the gas phase under special conditions of laser ablation of graphite with subsequent trapping of the target cyclocarbons followed by measurements of their electronic spectra. , These data open up possibilities for the astronomical search for cyclocarbons in diffuse clouds by absorption spectroscopy …”
Section: Structure Of C18br6 and C18(co)6 Precursors On The Nacl Surfacementioning
confidence: 99%
“…Ðorđević et al [ 1 ] reported the pre-synthetic and post-synthetic approaches for CDs synthesis and the influences of chemical tools on the properties of CDs. Wu et al [ 2 ] reviewed the synthesis of four types of CDs-based composites (metal-CDs, organic-CDs, nonmetallic inorganic-CDs, and multicomponent-CDs composites) and their uses in the bioapplications, such as biosensing, bioimaging, and drug delivery. Zhang et al [ 3 ] reviewed the development of synthetic/modification methods of CDs and CDs-based optical sensors for pesticides, as well as the advantages, possible limits, and challenges for their real-world application.…”
Section: Introductionmentioning
confidence: 99%